Relevansi Wahyu dan Akal sebagai Sumber Kebenaran dalam Pendidikan Islam - Angraeni, Yuli; Puja Khairunnisa, Salsa Bila; Rasyid, M.; Puspika Sari, Herlini (LP3M STAI Ibnurusyd, 2024)
In Islamic education, revelation is considered an absolute guideline that forms the foundation of values and morals, while reason functions as a means to understand and develop knowledge that is in line with Islamic principles. The descriptive-analytical approach in this study emphasizes the importance of balance between revelation and reason. The goal is to achieve holistic truth while forming students who are not only knowledgeable but also have noble character. The results of this study indicate that the synergy between revelation and reason has the potential to overcome the challenges of contemporary Islamic education, such as the demands of the development of science and technology, without ignoring religious principles. The integration of revelation and reason also has positive implications in the formation of character, ethics, and critical thinking skills of students. Thus, the development of Islamic education that unites revelation and reason can form a generation that has a balance between intellectuality and spirituality, and is able to face global challenges based on Islamic values.